STUDY OF ELECTROLUMINESCENCE OF STRUCTURE BASED ON ZnS:Cu,Cl WITH PHOTOCONVERTER Y3Al5O12:Ce - Leonid Vasilievich Mikhnev; Evgheny Alekseevich Bondarenko; Dmitry Petrovich Valyukhov; OlegMikhailovich Chapura; Alexey Alexandrovich Skomorokhov; Elena Vasilyevna Pankova; Ilia Vladimirovich Nemov; Egor Aleksandrovich Dyakov (Вестник Северо-Кавказского федерального университета, 2022)
The work presents the study of calorimetric and spectral parameters of radiation, generated with electroexcitation structure based on luminophore ZnS:Cu,Cl and layer of Yfl(O12:Ce. Basing on electroluminescence spectra of ZnS:Cu,Cl and photoexcitation spectra of Yfl(O12:Ce, we have made conclusion of usability of YflfO12:Ce for high efficiency transform ZnS:Cu,Cl electroluminescence in white light. Luminescence spectra of researched structure is measured into wide range of exciting voltage frequency. The frequency characteristic of electroluminescence is determined and limited frequency of exciting voltage for appearing of white light in the structure is established.